I'm trying to understand the basis of contradiction and I feel like I have understood the ground rules of it.

For example: Show that the square of an even number is an even number using a contradiction proof.

What I have is: Let n represent the number.

n is odd if n = 2k + 1, where k is any number

n is even if n = 2k, where k is any number

We must prove that if n^2 is even, then n is even.

How do I proceed on from here?

  • $\begingroup$ You have already posted a question about this not too long ago. $\endgroup$
    – fkraiem
    Feb 10, 2014 at 18:52
  • $\begingroup$ Hint: directly plug in $2k+1$ for $n$ then see that you receive a contradiction. You want to assume $n^2$ is odd for contradiction. $\endgroup$
    – user59999
    Feb 10, 2014 at 18:57
  • $\begingroup$ @Sentrl,you are welcome,please look on my answer,you simple should assume contradiction and you will see by this step how to apply this emthod $\endgroup$ Feb 10, 2014 at 19:08

2 Answers 2


We prove the contrapositive. In this case, we want to prove

$n^2$ even implies $n$ even

which is equivalent to the contrapositive

$n$ not even implies $n^2$ not even

or in other words

$n$ odd implies $n^2$ odd.

If $n$ is odd, then $n=2k+1$ then \begin{align*} n^2 &= (2k+1)^2 & \text{substituting in } n=2k+1 \\ &= 4k^2+4k+1 & \text{expanding} \\ &= 2(2k^2+2k)+1 \end{align*} which is odd, since it has the form $2M+1$.

We can essentially turn this into a proof by contradiction by beginning with "If $n$ is odd and $n^2$ is even...", then writing "...giving a contradiction" at the end. Although this should be regarded as unnecessary.

The other direction, i.e.,

$n$ even implies $n^2$ even

can also be shown in a similar way: If $n=2k$, then $n^2=(2k)^2=4k^2=2(2k^2)$ which is even.


If you insist by contradiction...then consider some $n$ that is even, then: $$n = 2k$$ Where $k$ is some natural number not $0$. Assume that $n^2$ is not even, but then contradicting the fact that $n^2 = (2k)^2 = 4k^2 = 2(2k^2)$ is even.

Alternatively, if $n^2$ is even but $n$ is odd, then $n = 2k+1$ so $$(2k+1)^2 = 4k^2 + 4k + 1 = 2(2k^2 + 2k) + 1$$ ...contradicting the fact that $n^2$ is assumed to be even.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.